2011
DOI: 10.1177/0020764011413669
|View full text |Cite
|
Sign up to set email alerts
|

Counselling and psychotherapy services in more developed and developing regions in China: A comparative investigation of practitioners and current service delivery

Abstract: In China, the level of socioeconomic development significantly influences the development of professional counselling and psychotherapy services. Important progress is evident in the field; however, the lack of systematic training and the scarcity of professional practitioners remain a challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Even when participants did acknowledge that China has counseling in high schools or colleges, it was characterized as scarce, unpopular, or ineffective. These results are somewhat discrepant with the extant literature, as researchers have noted the growth of counselor education and the proliferation of mental health resources since the Cultural Revolution (Qian et al, 2012). A rare finding within the domain was that participants felt that counseling services were more accepted in larger cities, a finding that is supported by extant research (Chang et al, 2005).…”
Section: Cultural Differences In Counseling Practicesmentioning
confidence: 79%
See 4 more Smart Citations
“…Even when participants did acknowledge that China has counseling in high schools or colleges, it was characterized as scarce, unpopular, or ineffective. These results are somewhat discrepant with the extant literature, as researchers have noted the growth of counselor education and the proliferation of mental health resources since the Cultural Revolution (Qian et al, 2012). A rare finding within the domain was that participants felt that counseling services were more accepted in larger cities, a finding that is supported by extant research (Chang et al, 2005).…”
Section: Cultural Differences In Counseling Practicesmentioning
confidence: 79%
“…Although counseling has become more socially acceptable, many Chinese citizens do not have access to psychological services. For example, mental health resources are often concentrated in urban areas, leaving some rural areas with a paucity of mental health professionals (Qian et al, 2012). Qian and colleagues (2012) reported that practitioners in rural areas had fewer years of experience and less advanced training.…”
Section: Counseling In Chinamentioning
confidence: 99%
See 3 more Smart Citations